2023
DOI: 10.1620/tjem.2023.j028
|View full text |Cite
|
Sign up to set email alerts
|

MiR-10b-5p Impairs TET2-Mediated Inhibition of PD-L1 Transcription Thus Promoting Immune Evasion and Tumor Progression in Glioblastoma

Abstract: Objective: Glioblastoma (GBM) is a highly aggressive primary brain tumor that shows intratumoral heterogeneity at the cellular and molecular level. Activation of programmed death receptor 1(PD-1) interaction with its ligand PD-L1 is a well-known mechanism requisite for immune evasion deployed by malignant tumors including GBM. Herein, we set out to dissect the mechanism explaining the regulation of PD-L1 gene expression in GBM. Methods:The clinical samples consisted of 37 GBM tissues and 18 normal brain tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…9c ). This miRNA has been identified that impairs TET2-mediated PD-L1 transcription inhibition, by which to promote immune evasion and tumor progression in glioblastoma 51 . By further integration of the TIDE score correlated miRNAs and the putative targets obtained from public resources, we constructed a miRNA immune evasive network to describe the mechanism explaining roles of miRNA involved in immune envision regulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…9c ). This miRNA has been identified that impairs TET2-mediated PD-L1 transcription inhibition, by which to promote immune evasion and tumor progression in glioblastoma 51 . By further integration of the TIDE score correlated miRNAs and the putative targets obtained from public resources, we constructed a miRNA immune evasive network to describe the mechanism explaining roles of miRNA involved in immune envision regulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis suggested that the possible underlying mechanism depends on the recruitment of histone deacetylases (HDAC1 and HDAC2) to PD-L1 promoter by TET2, as occupancy of the promoter site of these three enzymes was demonstrated. This study represents a valuable example that elucidates possible mechanisms of interconnections between multiple epigenetic components and their contribution to the overall cellular responding [51].…”
Section: Dna Demethylation and Mirnasmentioning
confidence: 99%
“…This suppression regulates TET2, which is downregulated in GBM, impacting the aggressiveness of GBM cells and their ability to evade the immune system. TET2 recruits HDAC1 and HDAC2 to the PD-L1 promoter, leading to the inhibition of PD-L1 transcription [ 152 ].…”
Section: Micrornas: Bridging the Gap Between Gene Regulation Immune C...mentioning
confidence: 99%